1986
DOI: 10.1007/bf01410636
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility of isotactic polypropylene with atactic polystyrene

Abstract: Abstract:The miscibility ofisotactic polypropylene-atactic polystyrene blends using dilatometric, TOA, DAT and stress-strain methods were studied. It appears that the blends are heterogeneous, having two glass transition temperatures. However, some interactions between components are evident to change the Tgs of their amorphous phases and the Tm of isotactic polypropylene crystals. The results are discussed on the basis of the blends' thermal and tensile properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…From the fact that the T c of PP decreased in the machine direction (MD) of the flexural specby PS blending, it was assumed that there was imen was measured with a micrometer and mold an interaction between PP and PS as reported by shrinkage was calculated by the following equaMucha. 23 The decrease of DH c by PS blending was tion: slightly lower than the theoretical value.…”
Section: Measurement Of Propertiesmentioning
confidence: 63%
See 1 more Smart Citation
“…From the fact that the T c of PP decreased in the machine direction (MD) of the flexural specby PS blending, it was assumed that there was imen was measured with a micrometer and mold an interaction between PP and PS as reported by shrinkage was calculated by the following equaMucha. 23 The decrease of DH c by PS blending was tion: slightly lower than the theoretical value.…”
Section: Measurement Of Propertiesmentioning
confidence: 63%
“…18,19 studied the melt spinning of PP/PS blends markedly decrease. Mucha 23 presumed that there and reported on the morphology and formation is an interaction between PP and PS because the mechanism of ultrafine fibrils 18 and their orientaglass transition temperature of PS increases and tion behavior and mechanical properties. 19 They the glass transition temperature and melting point of PP decrease when PS is blended with PP.…”
Section: Introductionmentioning
confidence: 98%
“…Using a fracture mechanics approach, the K c value was calculated from the slope of plots of P/BW vs. 1/YЉ, and forced through the origin to 1 under the same testing conditions as the notched specimens. Thermal and mechanical properties for the blends produced with the mild mixing screw are summarized in Table II.…”
Section: Fracture Toughness Measurementmentioning
confidence: 99%
“…In polymer blends where at least one component is crystallizable, the presence of the other component can have significant influence on its melting and crystallization temperatures, crystallite growth rate, and crystallinity. Particularly [1][2][3][4][5][6] with incompatible blends, several phenomena, such as induction of specific crystal modifications, rejec- 7 tion, engulfment, nucleation at the interface, and [8][9][10] deformation of the dispersed component by the growing spherulites of the matrix material have 8,11 been reported. For the case of PP/PS blends, several authors have concluded that there is a specific interaction between PP and PS at their interface in spite of their very low level of miscibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation